Flame size and volumetric heat release rate of turbulent buoyant jet diffusion flames in normal- and a sub-atmospheric pressure. (15th June 2015) - Hu, Longhua; Zhang, Xiaolei; Wang, Qiang; Palacios, Adriana
Highlights: Relationship between flame size and heat release rate obtained for jet diffusion flame. Unique data revealed for a sub-atmospheric pressure and compared with normal pressure. Non-dimensional global correlation proposed including HRR and pressure effect. Abstract: This paper investigates the flame size (i.e. envelop surface area and flame volume) and the volumetric heat release rate of turbulent jet diffusion flames, in both normal and in a sub-atmospheric pressure. Experiments on turbulent jet diffusion flames, produced with nozzles of 4, 5, 6 and 8 mm in diameter and using propane as fuel, have been carried out at two different altitudes: Hefei, 50 m and 100 kPa and Lhasa, 3650 m and 64 kPa. Results have shown both the flame envelope surface area, Af, and the flame volume, Vf, to be much larger in the sub-atmospheric pressure than in the normal pressure (i.e. Af  ∼  p − 4/5 ; Vf  ∼  p −7/5 ). The flame envelope surface area has been found to scale with the heat release rate, Q ̇, by the power of 4/5, Af  ∼  Q ̇ 4 / 5 . The flame volume, Vf, has also been found to scale with the heat release rate by the power of 9/10, Vf  ∼  Q ̇ 9 / 10 . The volumetric heat release rate, Q ̇ ‴, has been found to be a function of both the heat release rate, Q ̇, and the ambient pressure, p ( Q ̇ ‴ ∼ Q ̇ 0.1 ; Q ̇ ‴ ∼ p 7 / 5 ). General non-dimensional correlations for all the present data, obtained for the different nozzle diameters and the two ambient pressures, have also been proposed for the flame envelope surface area and the flame volume, respectively.